INTRA-RELIGIOUS DIALOGUE IN POST-SECTARIAN VIOLENCE: Assessing Sampang Sunni-Shiite Relation in Indonesia - Fiqh Vredian Aulia Ali (AL-TAHRIR, 2018)
Abstract : While there were various studies about Sampang Shiites which explore violence, exclusion, and conflict, the study analyzing intra-religious dialogue initiative and assessing the impact of it in enhancing Sunni-Shiite resolution in post-sectarian violence in Sampang, East Java, remains understudied. For this, I use Reina Neufeldt’s framework (2011) on “the theory of change” in interfaith dialogue and employs qualitative inquiry by conducting observation, interview, and documentation. This study argues that the inability of returning Sampang Shiite to their home is in line with insufficiencies of intra-religious dialog initiatives in dealing with Sunni-Shiite antagonism theologically, facilitating reconciliation politically, and intensifying civic engagement culturally to restore social and intersect relation. However, there is a hope of peace from intersecting grassroots reconciliation between the former perpetrators and victims by “the People Peace Charter” that significantly decreased Sunni-Shiite antagonism and segregation.الملخص: على الرغم من وجود العديد من الدراسات حول سامبانج الشيعية التي تستكشف العنف والاستبعاد والنزاع ، فإن الدراسات التي تحلل مبادرات الحوار بين الأعراق وتقييم تأثيرها على تحسين حل السني و الشيعي بعد العنف الطائفي في سامبانغ ، جاوة شرق ، لم تدرس. لهذا، استخدم أطر رينا نيوفلد (2011) عن "نظرية التغيير" في الحوار بين الأديان وباستخدام نهج نوعي للمراقبة، والمقابلات، والوثائق. وترى هذه الدراسة أن العقبات سامبانغ الشيعة يعود إلى قريتهم وفقا لمبادرة الحوار قيود بين الاديان في تعامل العداء بين السني والشيعي لاهوتيا، وتسهيل المصالحة السياسية وبناء السلام وتكثيف لاستعادة الربط بين طائفة الاجتماعي. ومع ذلك، هناك توقعات المصالحة الشعبية بين الجناة والضحايا السابقين ب "ميثاق السلام للشعوب" التي تعيد التفرقة والعداء بين السنة والشيعة.Abstrak: Meskipun ada berbagai studi tentang Syiah Sampang yang mengeksplorasi kekerasan, eksklusi, dan konflik, studi yang menganalisis inisiatif dialog antarsekte dan menilai dampaknya dalam meningkatkan resolusi Sunni-Syiah pasca kekerasan sektarian di Sampang, Jawa Timur, masih belum dikaji. Untuk ini, saya menggunakan kerangka kerja Reina Neufeldt (2011) tentang “teori perubahan” dalam dialog antaragama dan menggunakan pendekatan kualitatif dengan observasi, wawancara, dan dokumentasi. Studi ini berargumen bahwa kendala mengembalikan Syiah Sampang ke kampung halaman mereka sejalan dengan keterbatasan inisiatif dialog intrareligious dalam menangani antagonisme Sunni-Syiah secara teologis, memfasilitasi rekonsiliasi secara politis, dan mengintensifkan bina-damai secara kultural untuk mengembalikan pertalian antar-sekte. Namun, ada harapan dari rekonsiliasi akar-rumput antara para mantan pelaku dan korban dengan “Piagam Perdamaian Rakyat” yang secara signifikan mengurangi segregasi dan antagonisme Sunni-Syiah.